(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Education is the most powerful tool which can shape the destiny of anindividual as well as the whole nation. It is pity that our great nation failedto eradicate the menace of illiteracy even after 65 years of independence. Itwas 86th constitutional amendment made by the parliament and article 21A in theyear of 2002 which made Right to Education a fundamental right. This act boundsall the stakeholders like parents, schools, society, states as well as centralgovernments to play their roles in order to provide free and compulsoryeducation to the children between the 6-14 yrs of age. In India Acts are framedbut they are not implemented with the true spirit. There are several issues andchallenges which still need to explore and discuss for the successfulimplementation of Right to Education Act.